Hubungan Stres Psikologis Terhadap Timbulnya Akne Vulgaris - Arifah Afkar Fadilah (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Introduction: Acne vulgaris is an inflammatory disease owned by various age groups, especially adolescents. This disease occurs due to multifactorial triggers and stress factor is one of that things. Objective: Giving knowledge and understanding of the relation of psychological stress to the incidence of acne vulgaris. Method: Using a literature study from several national and international journals that have been published then the results are compared and presented in the article. Result: Stress can affect physiological conditions the body will respond to it through the hormonal system that plays a role in the etiopathogenesis of acne vulgaris. Conclusion: Psychological stress is related to the incidence of acne vulgaris.